A Two-Year Study of The Frequency of Rhesus Phenotype and Probable Genotype in a tertiary Care Hospital at Dhaka, Bangladesh (Bangladesh Critical Care Journal, 2025)
Background: The Rhesus system is a major blood group system like the ABO system. Despite proper blood grouping and cross-matching, recipients can develop Rhesus antibodies, leading to Hemolytic Disease of the Newborn (HDN) or Delayed Hemolytic Transfusion Reactions (DHTR). Rhesus-negative individuals are particularly at risk if exposed to Rhesus-positive red cells through transfusion or pregnancy. Identifying Rh phenotypes and potential genotypes can significantly help in preventing alloimmunization and adverse reactions in patients receiving multiple transfusions. Objective: To assess the frequency of Rh antigens phenotype and most probable genotype in the Bangladeshi population. Method: This cross-sectional study was conducted with 325 randomized samples from both patients and donors at the Transfusion Medicine Department of BIRDEM General Hospital from January 2020 to December 2021. Samples were tested for Rh antigens phenotype and most probable genotype by using the tube agglutination method. The Anti-Human Globulin Test (AHGT) was performed as needed or in specific situations. Results: Out of the 325 blood samples, 167 (51.2%) were from males and 158 (48.8%) were from females. Incidence of Rh D positive were 94.12% (306 samples) and 5.88% (19 samples) belong to Rh D negative. The most common genotypes among Rh D positive samples were DCe/DCe (R1R1)- 41.84%, DCe/dce (R1r) -28.61%, DCe/DcE (R1R2)- 19.07%, and dce/dce (rr)- 3.38%. Rare genotypes of Rh D positive individuals detected in our study included DcE/dce (R2r)-1.84%, DCe/DCE (R1Rz) -1.23%, Dce/dce (R0r)- 0.92%, and DcE/DcE (R2R2) - 0.61%. Among Rh D negative samples, the detected rare genotypes were dCe/dce (r’r) - 1.89% and dcE/dce (r”r) - 0.61%. Conclusion: There is significant racial and geographical variation in the frequency of Rh phenotypes and genotypes. The Rh blood group system is essential for developing strategies to prevent Rh sensitization in clinical transfusion practices. Additionally, it can be valuable for addressing medico-legal issues and conducting genetic studies in Bangladesh.Bangladesh Crit Care J March 2025; 13 (1): 30-34